1991
DOI: 10.1002/clc.4960140608
|View full text |Cite
|
Sign up to set email alerts
|

Prazosin in Chronic Congestive Heart Failure Due to Ischemic Heart Disease

Abstract: Summary:Oral prazosin hydrocholoride (2-20 mglday) was administered to 38 patients with chronic congestive heart failure due to ischemic heart disease for 6-18 months. Half (19) of the patients were hypertensive and half ( 19) nonhypertensive. All were receiving furosemide (80 nig/day, orally) and 19 were receiving digoxin (0.25-0.5 mglday, orally) in addition to prazosin. Clinical radiological, mechanocardiographic, echocardiographic, and biochemical observations were made initially, at peak response, and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The protein NQO2 was associated with a decreased risk of HF, through the amino acid breakdown product indoleacetylglutamine. Prazosin, which acts as an adrenergic receptor alpha-1 antagonist and targets NQO2, has shown potential benefits for HF patients in previous observational studies and trials (40,41), suggesting prazosin might be a relevant repurposing candidate for HF.…”
Section: Discussionmentioning
confidence: 99%
“…The protein NQO2 was associated with a decreased risk of HF, through the amino acid breakdown product indoleacetylglutamine. Prazosin, which acts as an adrenergic receptor alpha-1 antagonist and targets NQO2, has shown potential benefits for HF patients in previous observational studies and trials (40,41), suggesting prazosin might be a relevant repurposing candidate for HF.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, several clinical investigations have revealed the advantageous effects of α 1 -AR antagonists including prazosin in failing hearts due to different etiologies [ 90 , 91 , 92 , 93 ]. It should be mentioned that while co-administration of prazosin and metoprolol in heart failure was observed not to exert any additive effects [ 94 ], the results of the COMET trial (Carvedilol or Metoprolol European Trial), revealed a greater benefit of carvedilol in heart failure than with metoprolol alone [ 95 ].…”
Section: Evidence For Regression Of Abnormal Cardiomyocyte Growth By ...mentioning
confidence: 99%
“…The efficiency of Terminalia arjuna therapy in ischemic stroke and ischemic heart diseases has been studied by several groups of researchers. In a study, 20g bark stem powder was administered in three divided doses to patients of angina and thrombotic stroke [88]. Functional improvement in motor power along with an increase in prothrombin time was noted in these cases.…”
Section: Anti-ischemic Activitiesmentioning
confidence: 99%